Comparison of Scientific Socio-Economic Research Performances in Eastern European Universities - Carmen Anton; Nelu Florea; Silviu-Mihail Tiþ\~a (CES Working Papers, 2012)
Scientific research performance measurement and its analysis creates the context where universities are forced to develop strategies to increase the values obtained from indicators such as number of scientific articles, the number of citations of these articles, h-index, g-index, etc. The purpose of this article is to analyze the performance differences arising in the socio-economic science between major universities in South-Eastern Europe, many of them EU Members. In addition, to see where they stand compared to Western Europe, will include a brief review of the results of a major university as London School of Economics and Political Science.
Keywords: I23; L2; L8; 330; performance measurement; indicators; Southeastern Europe; database of scientific articles Romania